Twitching motility of Stenotrophomonas maltophilia under iron limitation: In-silico, phenotypic and proteomic approaches - Vasodavan, Kalidasan; Neela, Vasantha Kumari (Landes Bioscience, 2020)
This study investigates the twitching ability of 28 clinical and five environmental strains of S. maltophilia grown under iron-depleted condition through in-silico, phenotypic and proteomics approaches. Rapid Annotations using Subsystem Technology (RAST) analysis revealed the presence of 21 targets of type IV pilus shared across S. maltophilia strains K279a, R551-3, D457 and JV3. The macroscopic twitching assay showed that only clinical isolates produced a zone of twitching with a mean of 22.00 mm under normal and 25.00 mm under iron-depleted conditions. (p = 0.002). Environmental isolates did not show any significant twitching activity in both conditions tested. Isobaric Tags for Relative and Absolute Quantification (ITRAQ) analysis showed altered expression of twitching motility protein PilT (99.08-fold change), flagellar biosynthesis protein FliC (20.14-fold change), and fimbrial protein (0.70-fold change) in response to iron-depleted condition. Most of the strains that have the ability to twitch under the normal condition, exhibit enhanced twitching during iron limitation.